The effect of therapeutic communication based on Peplau's model on body image and pain among cancer patients undergoing radiotherapy in the Parsian hospital of Shahrekord - Shekoufeh Naderi Samani; Ali Hasanpour Dehkordi; Shahriar Salehi Tali (Shahrekord University of Medical Sciences, 2024)
Background and aims: Cancer has significant effects on the lives of cancer patients and their families, so effective communication skills are an integral part of the process of caring. This study aims to investigate the effect of Peplau's Therapeutic communication model on body image and pain among cancer patients. Methods: The present research is a quasi-experimental study conducted with the attendance of 64 cancer patients undergoing radiotherapy in Shahrekord Parsian Hospital in 2020-2021. First, the research units were selected purposefully and then randomly assigned to intervention and control groups. In the intervention group, Peplau's nursing model was done in four stages individually. Data collection tools were a demographic survey questionnaire, McGill Pain Questionnaire, and Body Image Questionnaire (MBSRQ). The mean scores before, immediately after, and three months after were compared using SPPS version 24 software. Results: Before interfering, the results of the study indicated the standard deviation±mean of body image scores in control and intervention groups were respectively 204.81±2.79, 206 (217-75.187)+that were not significantly different from each other (P≥0.568). Whereas these scores immediately and three months after had statistically significant differences from each other (P<0.01). The results also indicated that the Standard deviation±mean of pain scores in control and intervention groups were 59.56±0.793 and 58.25±0.627 were not significantly different (P≥0.248). However, these scores immediately and three months after had statistically significant differences from each other (P<0.01). Conclusion: The findings of this research showed that implementing Peplau's theory can improve body image and decrease pain in patients. Due to this program's effectiveness, low cost, and safety, it is recommended for consideration in the nursing care program